(untitled) (Ius Novum, 2020)
The article presents the issue of control of apartment owners’ resolutions in terms of their correctness. In the author’s opinion, the presently binding legal regulations guarantee apartment owners reliable, stable, legal and rational management of their common real property. In the most important matters that are beyond the standard management, there is a statutory obligation to adopt a resolution by the majority vote of apartment owners. Each owner is entitled to appeal against such resolution due to its non-compliance with the provisions of law or the owners’ agreement, or if it breaches the principles of appropriate common real property management, or infringes the owners’ interests. These statutory safeguards constitute sufficient protection against activities undertaken by the managing body that are in conflict with the interests of most owners or to the detriment of any of the owners.